Gestión del talento humano y su incidencia en las ventas del Retail H & M Trujillo, 2020 - Bailón Calderón, Anthony Eduardo Moisés (2021)
This study sought to determine how Human Talent Management had an impact on retail sales H & M Trujillo, 2020. For which it was based on a cross-sectional explanatory study, under a non-experimental design using the deductive and descriptive method, for which a survey was applied to 70 employees of H&M Trujillo, and a documentary review was also used for the sales variable. As results, it was obtained that the impact of the identification of critical positions, the training of competencies, the development and management of rewards in retail sales was an standardized beta of -5.2%, 26.6%, 17.5% and 49.4%, respectively. , although, for the first and third dimensions the relationship was not significant, stating that the incidence of the constructs was direct and significant. Concluding that, the impact of human talent management on retail sales was 40.4% and it turned out to be significant at the 5% level.